The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/tera.1420490408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the class III Antiarrhythmic, Dofetilide (UK‐68,798) on the heart rate of midgestation rat embryos, in vitro

Abstract: Gestation day 11 (GD11) and 14 (GD14) embryos were cultured for up to 4 hours in the presence of Dofetilide (0.01-0.50 microgram/ml), a potent Class III Antiarrhythmic which selectively inhibits the rapid component of the time dependent outward potassium current (IKr). Significant (P < or = 0.05) reductions in heart rate (HR) as measured over a 4 hour period were dose dependent and reversible. The sensitivity of the GD11 embryos was greater than GD14 embryos (14-64% decrease in HR vs. an 11-43% decrease in HR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Developmental toxicity occurred at doses causing no adverse effects in the mothers, with the exception of the two deaths that will be discussed later in this section. The observed sotalol-induced embryonic death in this study is in accordance with what has been shown for other Ikr blockers in studies in rats (Ban et al 1994;Spence et al 1994;Marks & Terry 1996;Webster et al 1996) and in mice (Skö ld & Danielsson, 2000). Single-dose administration during Day 9, 10, 11, 12, 13, or 14 of the selective Ikr blockers dofetilide and almokalant in rats (Spence et al 1994;Webster et al 1996) resulted in embryonic death.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Developmental toxicity occurred at doses causing no adverse effects in the mothers, with the exception of the two deaths that will be discussed later in this section. The observed sotalol-induced embryonic death in this study is in accordance with what has been shown for other Ikr blockers in studies in rats (Ban et al 1994;Spence et al 1994;Marks & Terry 1996;Webster et al 1996) and in mice (Skö ld & Danielsson, 2000). Single-dose administration during Day 9, 10, 11, 12, 13, or 14 of the selective Ikr blockers dofetilide and almokalant in rats (Spence et al 1994;Webster et al 1996) resulted in embryonic death.…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that Ikr channels are expressed and functional when the embryonic heart starts beating, which occurs on Day 9.6 in the rat (Ban et al 1994). The results also suggest that the rabbit is a sensitive species for induction of developmental toxicity of Ikr blockers in the same way as has previously been shown for the mouse and the rat (see above) (Spence et al 1994;Webster et al 1996). However, in contrast to the rat where the Ikr channel is most likely suppressed in favour of other repolarisation ion channels on Days 14-15, developmental toxicity was also observed on Days 15-16 in the rabbit.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This idea has been supported by the observation of embryotoxic effects in pregnant rats, where application of IKr specific channel blocker, dofetilide, has been described to strongly impair the rhythm of embryonic hearts with lethal effects (Spence et al,1994;Webster et al, 1996). To explore the expression pattern of the IKr forming components KCNH2 (hERG) and KCNE2 (MiRP1), we analysed, by means of in situ hybridization, sagittal and transversal sections in late rat embryonic development.…”
Section: Discussionmentioning
confidence: 99%